Updated consumer risk assessment of fluoride in food and drinking water including the contribution from other sources of oral exposure - EFSA Scientific Committee; Susanne Hougaard Bennekou; Ana Allende; Angela Bearth; Josep Casacuberta; Laurence Castle; Tamara Coja; Amélie Crépet; Ron Hoogenboom; Helle Knutsen; Claude Lambré; Søren Saxmose Nielsen; et al. (EFSA Journal)
Abstract This updated risk assessment evaluated evidence on potential adverse health effects of fluoride related to all sources of oral exposure as mandated by the European Commission. Fluoride benefit assessment was not included. Effects on the central nervous system, thyroid and bone were prioritised. Evidence from human studies indicates that total fluoride intake is associated with adverse effects on the developing brain at drinking water concentrations > 1.5 mg/L. The evidence of such associations below 1.5 mg/L was not sufficiently consistent to draw conclusions for risk assessment. Using drinking water concentration of 1.5 mg/L as a reference point, a safe level of intake including all sources of oral exposure of 3.3 mg/day was established for pregnant women to protect the fetus. This safe level of intake was extended to apply to other adults and children > 8 years. It is considered protective also against possible adverse effects on thyroid function and bone mineralisation, for which associations have been observed at water concentrations > 1.5 mg/L. Dental fluorosis was considered the most sensitive endpoint for children ≤ 8 years. Tolerable upper intake levels (UL) of 1.0, 1.6 and 2.0 mg/day were established for infants, toddlers and children 4–8 years, respectively. These ULs are considered protective against other possible adverse effects of fluoride, including neurodevelopmental outcomes. Aggregate exposure included intake of fluoride from food, drinking water, discretionary salt and (ingested) dental care products. Aggregate exposure based on the mean concentration of fluoride in EU drinking water (submitted data) was below the above health‐based guidance values (HBGVs) for all age groups. Aggregate exposure exceeds the HBGVs at the 95th percentile of intake in the scenario of the P95 concentration of fluoride in EU drinking water, for all age groups except adolescents. The risk assessment suggests that the current legal limit for drinking water (1.5 mg/L) in the EU is not sufficiently protective.